METHODOLOGY FOR DEVELOPMENT OF SPECIAL PHYSICAL QUALITIES OF 10–12-YEAR-OLD VOLLEYBALL PLAYERS - Abdilhakim Jumaev (Proximus Journal Publishing, 2024)
This paper presents and experimentally tested the methodology for the development of special physical qualities of volleyball players aged 10-12 years, as well as the results obtained during the pedagogical experiment.it contains material reflecting new practice data and the results of scientific research that reveal the issues of physical fitness of volleyball athletes aged 10-12.
Keywords: physical fitness; volleyball athletes; physical qualities; means and methods of training